QUALITATIVE STUDIES OF CREAM CHEESE MADE BY USING BIFIDOBACTERIUM BIFIDUM & LACTOBACILLUS ACIDOPHILUS - HUSSAIN, A; INAYAT, S; AHMAD, F; RASHID, S; REHMAN, B; SAEED, I (Biological and Clinical Sciences Research Journal, 2024)
World is facing a lot of health problems especially in under developed countries of Asia. This crucial situation demands beneficial foods. This study was planned to produce quality Cream cheese. Probiotic Cream cheese had been promoted for health benefits by using Bifidobacterium bifidum & Lactobacillus acidophilus. Buffalo milk was used to produce Cream cheese. Five treatments were handled; T₀ was the regular treatment in which yoghurt culture was inoculated to make Cream cheese while a combination of yoghurt as well as Bifidobacterium bifidum & Lactobacillus acidophilus was inoculated in T1, T2 and T3. Besides T4 was produced by using only Bifidobacterium bifidum & Lactobacillus acidophilus. In the process milk was standardised up to 5% milk fat then it was pasteurized (63°C for 30 minutes). Cooled to 42°C and 2% starter culture was inoculated in that mixture. After incubation the pH reached up to 4.6. Salt (0.5-1%) was added and product packed into plastic cups and stored (4°C, 4 weeks). Qualitative study of the product showed that T4 treatment was better as compare to T₀, T1, T2 and T3. Conclusively, probiotic Cream cheese produced by using buffalo milk is beneficial for reducing health problems like gastric problems, colon cancer etc. This product can play a vital role in functional foods industry as well as cheese industry.